A study on the cross-section data of 43, 44m, 46, 47Sc isotopes via (d, x) reactions on natural abundance targets under the effects of deuteron optical models. (April 2023) - Şekerci̇, M.; Özdoğan, H.; Kaplan, A.
Abstract: Many studies have investigated the influence of theoretical models and factors involved in the acquisition of cross-section data of a nuclear reaction. The implications of different models of various variables such as level density, gamma strength function, and optical potentials on cross-section calculations whether used solo or jointly are investigated in a significant portion of the works conducted in this perspective. The aim of this particular study is to investigate the influence of different optical models on the cross-section calculations in production of several scandium isotopes, known for various medical uses, from several targets with natural abundances by (d, x) reactions. For this purpose, the cross-section calculations using five available deuteron optical models of TALYS code in nat Ti(d, x) 43 Sc, nat Ti(d, x) 44m Sc, nat Ti(d, x) 46 Sc, nat Ti(d, x) 47 Sc, nat V(d, x) 47 Sc and nat Cr(d, x) 47 Sc reactions were performed and the obtained calculation results were compared with the experimental cross-section data gathered from the literature. To understand whether there is a significant and consistent relationship between the experimental data and the calculation results, both have been plotted together and analyzed with the naked-eye. In addition, the calculations of the mean standardized deviation, the mean relative deviation, the mean ratio and the mean square logarithmic deviation were performed in order to evaluate the results numerically. Highlights: Cross-section calculations were done for (p, x) 43, 44m, 46, 47 Sc reactions. TALYS 1.95 code was used for the calculations. Deuteron optical model potentials were used in calculations. Calculation results and available experimental data from the literature were compared. Also numerical comparisons have been done by using deviation factors.